Nick Srnicek’s Platform Capitalism: Crisis — Response — Boom — Crisis — and Response Again. What Do We Know about the Digital Economy? - David Khumaryan (Journal of Economic Sociology, 2019)
Nick Srnicek writes a convincing history of the modern digital economy, which has managed to develop numerous myths, hoaxes, and prescientific interpretations. Critical reconstruction of the events that preceded the birth and explosive growth of the digital technologies and products market, on the one hand, avoids their perception and understanding in the self-evident logic of the field (market), and on the other hand, provides an opportunity to perceive the future of digital capitalism. Srnicek is consistently detached from an optimistic view of the economy of the recent past and the near future. However, his argument does not involve discussions between “technopessimists” and “technoptimists,” rather Srnicek analyzes the digital economy and the model of platforms in the logic of a capitalist mode of production and a ruthless competitive race. Its intrinsic logic determines the sequence of economic agents’ actions and the possible image of the future. The crisis dynamics of capitalism of the last decades provide limited space for historical maneuvering and less and less space for political action, so any normative statements mostly lose their power. The analysis focuses on the business model of platforms from the perspective of the historical logic of capitalism aimed at seeking a new source of profitability in the condition of market exhaustion. This condition leads to a redefinition of PO the key categories of perception of the role of technologies in everyday life and in the scale of the economic system in terms of political economy. The reviewer gives a patient exposition of the basic concepts of the book and the theses on which Srnicek’s analysis is based. The text is mainly focused on the reconstruction of the main point of the book but also appeals to an important author for Srnicek, the historian Robert Brenner. The review concludes with a modest critical commentary on the book and a call for a Russian-language discussion of the book, which has already become very influential abroad.